A lamin‐like protein OsNMCP1 regulates drought resistance and root growth through chromatin accessibility modulation by interacting with a chromatin remodeller OsSWI3C in rice. Issue 1 (13th April 2020) - Yang, Jun; Chang, Yu; Qin, Yonghua; Chen, Dijun; Zhu, Tao; Peng, Kaiqing; Wang, Huaijun; Tang, Ning; Li, Xiaokai; Wang, Yusen; Liu, Yinmeng; Li, Xianghua; et al.
Summary: Lamin proteins in animals are implicated in important nuclear functions, including chromatin organization, signalling transduction, gene regulation and cell differentiation. Nuclear Matrix Constituent Proteins (NMCPs) are lamin analogues in plants, but their regulatory functions remain largely unknown. We report that OsNMCP1 is localized at the nuclear periphery in rice ( Oryza sativa ) and induced by drought stress. Os NMCP1 overexpression resulted in a deeper and thicker root system, and enhanced drought resistance compared to the wild‐type control. An assay for transposase accessible chromatin with sequencing (ATAC‐seq) analysis revealed that OsNMCP1‐overexpression altered chromatin accessibility in hundreds of genes related to drought resistance and root growth, including OsNAC10, OsERF48, OsSGL, SNAC1 and OsbZIP23 . OsNMCP1 can interact with SWITCH/SUCROSE NONFERMENTING (SWI/SNF) chromatin remodelling complex subunit OsSWI3C. The reported drought resistance or root growth‐related genes that were positively regulated by OsNMCP1 were negatively regulated by OsSWI3C under drought stress conditions, and OsSWI3C overexpression led to decreased drought resistance. We propose that the interaction between OsNMCP1 and OsSWI3C under drought stress conditions may lead to the release of OsSWI3C from the SWI/SNF gene silencing complex, thus changing chromatin accessibility in the genes related to root growth and drought resistance.